DAMPAK INTENSITAS ASET TETAP DAN PERSEDIAAN TERHADAP MANAJEMEN PAJAK - Basuki Toto Rahmanto (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Companies that carry out valid tax management can cause a low reported tax burden. By knowing the impact of fixed asset intensity and inventory intensity on tax management for the purpose of this research was conducted.This study uses control variables that are thought to influence tax management to support the conclusions, namely profitability, liquidity, and the number of independent commissioners.The research population is all mining companies listed on the Indonesia Stock Exchange in 2016–2020.The sample selection used purposive sampling technique.The results obtained were a sample of 9 companies, a total of 45 observational data.The research method uses multiple linear regression analysis. The research findings obtained the effect of fixed asset intensity and inventory intensity affecting tax management by controlling the variables of profitability, liquidity, and the number of independent commissioners. Keywords: Tax Management, Asset Intensity